Ecce Homo : Behold the Man. - Rinckhout, Eric ([S.l.] : Hannibal Publishing, 2017)
Creten, Johan ; Janssens, Ann Veronica ; Martin, Kris ; Nkanga, Otobong ; Van Oost, Jan ; Westphal, Sarah ; Muller, Sofie ; Braeckman, Dirk ; Alÿs, Francis ; Brey, Ricardo ; Kuijken, Sophie ; Tuymans, Luc ; Bellinkx, Ruben ; Benhelima, Charif ; Bervoets, Fred ; Bogaert, Thomas ; Brodahl, Cris ; Buggenhout, Peter ; Delrue, Ronny ; Delvoye, Wim ; De Meyer, Peter ; De Wilde, Johan ; Du Bois, Arpaïs ; De Cordier, Thierry ; Fabre, Jan ; Fierens, Kris ; François, Michel ; De Cupere, Peter ; Geers, Kendell ; Hanssen, Karin ; Heck, Kati ; Jabbar, Haider ; Lerooy, Thomas ; Meuris, Wesley ; Pinckers, Max ; Samyn, Fabrice ; Schacht, Kelly ; Van Bossche, Guy ; Van Caeckenbergh, Patrick ; Van de Moortel, Joris ; Vandenberg, Philippe ; Van der Auwera, Emmanuel ; Van Kerckhoven, Anne-Mie ; Van Imschoot, Jan ; Vanriet, Jan ; De Bruyckere, Berlinde ; Lafontaine, Marie-Jo ; Manders, Mark ; Borremans, Michaël ; Kiefer, Gideon ; 't Jolle, Sven ; Panamarenko ; De Vos, Kasper ; Boon, Elke Andreas ; Cotteleer, Anton ; Gasparotto, Lara ; Geerts, Elizabeth ; Van de Velde, Rinus ; Villavicencio Pizango, Shirley ; Tahon, Johan ; Aguirre y Otegui, Philip ; Dujardin, Filip
Ecce Homo. Behold the Man, Geukens & De Vil, Antwerp, 17/11/2017 - 25/02/2018
boek